(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2016)
The Druk Holding and Investments (DHI), a government holding company in Bhutan that owns and manages majority of the state owned enterprises and holds government shares in many of the publically listed companies, has been initiating corporate governance and performance management reforms over the last eight years since its establishment in November 2007. Introduction of corporate governance practices in line with international good practices and introduction of performance management system in the state owned companies called for managing change. This paper, after a general introduction of the concept of change management, shares the experiences in change management. The paper highlights some of the initiatives undertaken by DHI and its companies, and underscores that success of introducing a new system is more certain when changes are introduced through a consultative process.